Magical Realism in The Madrigal Family in Film Encanto (2021) - Danang Putra Pratama Mario (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Encanto (2021) is a movie set in a village in the mountains of Colombia. Encanto has a family background where each family member has magical gifts that are useful to help the villagers. The magical realism aspect in this movie is very thick which makes the researcher make this movie as the object of research. The problem that needs to be solved in this research is to explore the elements of magical realism in Encanto (2021) and how the elements of magical realism are depicted. This research is a descriptive qualitative research. In this research, Encanto movie by Jared Bush and Byron Howard is used as the data source. To support this research, e-books, e-journals, articles, and other online sources relevant to magical realism are used. The result of this research shows that all elements of Wendy B Faris' magical realism such as irreducible elements, phenomenal world, unsettling doubts, merging realms, disruption of space, time, and identity can be identified in the movie. The depiction of magical realism in this film is shown in several magical phenomena that occur. The combination of realistic phenomena with magic is used to convince that this story is true. There is also a decentered ideology in the film that depicts the third world. Keywords: Magical realism; Five characteristic; Encanto.